A unique miracle - "Khan Saniyasnain" (INDIA, Good word kidz, 2009)
The book narrates the story of Prophet Isa (Jesus) (peace be upon him), focusing on the miraculous events surrounding his birth and early life. It highlights the signs and miracles that Allah bestowed upon him, emphasizing themes of faith, trust in Allah, and the importance of following His guidance. Through simple text and vibrant illustrations, the story captivates young minds, making complex concepts more relatable and understandable.